2023
DOI: 10.21203/rs.3.rs-3654644/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social exclusion and short video addiction in Chinese college students: The mediating role of boredom and self-control

Yali Zhang,
Ruohan Bu,
Jinxia Zhao
et al.

Abstract: Background Short video apps are very popular among Chinese college students, and some students even rely on them. Most of the current research only focuses on Internet addiction, and seldom pays attention to the phenomenon of short video addiction. Its influencing factors and formation mechanism are worth exploring. Objectives This study aims to explore the relationship between social exclusion and short video addiction among college students, and the mediating roles of boredom and self-control. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The study provided evidence that self-control acts as a partial mediator in the relationship between neurotic personality tendencies and the excessive use of short video clips, thus, supporting Hypothesis 2. Gugushvili et al (2022) noted that neuroticism was associated with low self-control consistent with previous studies while Zhang et al (2023) found that there is a significantly negative relationship between self-control and excessive use of short videos. The limited strength theory suggests that self-control is essentially limited; thus, negative emotions can deplete the levels of self-control (Muraven & Baumeister, 2000).…”
Section: Mediating Role Of Self-control and Flowsupporting
confidence: 81%
“…The study provided evidence that self-control acts as a partial mediator in the relationship between neurotic personality tendencies and the excessive use of short video clips, thus, supporting Hypothesis 2. Gugushvili et al (2022) noted that neuroticism was associated with low self-control consistent with previous studies while Zhang et al (2023) found that there is a significantly negative relationship between self-control and excessive use of short videos. The limited strength theory suggests that self-control is essentially limited; thus, negative emotions can deplete the levels of self-control (Muraven & Baumeister, 2000).…”
Section: Mediating Role Of Self-control and Flowsupporting
confidence: 81%